Comparative Transcriptome Analysis of Hard and Tender Fruit Spines of Cucumber to Identify Genes Involved in the Morphological Development of Fruit Spines - Lv, Duo; Wang, Gang; Zhang, Qi; Yu, Yao; Qin, Pei-Chao; Pang, Jin-An; Sun, Jing-Xian; Zhang, Ke-Yan; He, Huan-Le; Cai, Run; Pan, Jun-Song (Frontiers in Plant Science, 2022)
The Spines on cucumber fruit not only has important commercial value but also is a classical tissue to study cell division and differentiation mode of multicellular trichomes. It has been reported that CsTs (C-type Lectin receptor-like kinase) can influence the development of fruit spines. In this study, we took a pair of cucumber materials defined as hard (Ts, wild-type) and tender spines (ts, mutant), defined the developmental process of fruit spines as four stages (stage I to stage IV) by continuously observing by microscope and SEM. Comparion of transcriptome profilings in different development stage of wild-type spines showed 803 and 722 genes were up-regulated in stalk (stage II and stage III) and base (stage IV) development stage of fruit spines, respectively. The function analysis of DEGs showed that genes related to auxin polar transport and HD-ZIP transcription factor are significantly up-regulated during development of stalk. bHLH transcription factors and cytoskeleton related genes were significantly up-regulated during development of base. In addition, stage III is the key point for difference between wild-type and mutant. We detected 628 DEGs between wild-type and mutant at stage III. These DEGs are mainly involved in the calcium signaling of the cytoskeleton and auxin polar transport. Coincidentally, we found CsVTI11, a factor involved in auxin signal transmission, can interact with CsTs both in in vivo and in vitro, but this interaction does not exist between CsVTI11 and Csts, further suggested that CsTs may regulate the development of fruit spines by influencing cell polarity. These results provide useful tools to study the molecular networks associated with cucumber fruit spines development and elucidate the biological pathways that C-type Lectin receptor-like kinase plays in regulating the development of fruit spines.